The importance of relational values in gaining people’s support and promoting their involvement in social-ecological system management: A comparative analysis - Uehara, Takuro; Sakurai, Ryo; Hidaka, Takeshi (Frontiers in Marine Science, 2022)
People’s support and involvement are critical to the sustainable use and conservation of social-ecological systems (SESs). Integrating people’s values into management decisions is pivotal. Without proper integration, the resulting SES may not align with their desires and may not be supported by people. Furthermore, values can be a deep leverage point within a system that is difficult to change, as people may be more willing to be involved in activities that support what they value. Recent studies have illustrated the importance of relational values as the third value class (in addition to instrumental and intrinsic). Relational values are preferences, principles, and virtues associated with human-nature relationships. Although studies on relational values are available, empirical studies, particularly studies about the usefulness of relational values in promoting pro-SES behavior, are rare. Consequently, our study administered questionnaires to residents in three SESs in Japan (N = 864, 1136, and 1000, respectively) to understand how relational values impact people’s support and involvement in SES management as measured by pro-SES behavior scales. In addition, due to the lack of pro-SES behavior measurements, we developed measurement items and a development guideline. Our findings support previous theoretical discussions positing that relational values are critical as a single value class or as part of the plural values and need to be integrated into SES management decisions to gain people’s support. Furthermore, our study demonstrated that cultivating relational values could promote pro-SES behavior to realize a desirable state of SES. Although from the viewpoint of residents, relational values overlapped with instrumental and intrinsic values; however, as per theoretical discussions, the results indicated that relational values were important in their own right as they were well associated with pro-SES behavior scales. The findings were similar across the three SESs, with different social-ecological characteristics. In summary, managers must integrate relational values into management decisions to gain people’s support and should cultivate relational values to promote pro-SES behavior, in order to realize a desirable state of SES.